Commutation Methods of AC-AC Converter for Wind Power Generation System - Tammaruckwattana, S.; Kawpukdee, P.; Suppaadirek, N.; Gullayanono, R.; Rerkratn, A. (My University, 2022)
In this paper, the AC-AC converters using 2-step current commutation, 4-step current commutation, 2-step voltage commutation, 4-steps voltage commutation, and 3-steps voltage-current commutation will be used for a power converter system are proposed. The system is simulated and calculated with MATLAB/Simulink. This paper discusses each method, its difference, and its power loss.
Keywords: Commutation method; Matrix converter; Simulation; Switching loss